The Effect of Grafting Density on the Crystallization Behaviors of Polymer Chains Grafted onto One-Dimensional Nanorod - Tongfan Hao; Yongqiang Ming; Shuihua Zhang; Ding Xu; Zhiping Zhou; Yijing Nie (Advances in Polymer Technology)
The crystallization behaviors of five polymer chain systems grafted on a nanorod and the corresponding effect of grafting density were investigated by dynamic Monte Carlo simulations. The segment density near the interfacial regions, the number of crystallites, and the mean square radius of gyration (<Rg2>) increase with increasing grafting density, which are beneficial to the enhancement of crystallizability. Meanwhile, the crystalline morphology is greatly influenced by grafting density and polymer-nanorod interaction. For the grafted system with 52 chains, a nanohybrid shish-kebab (NHSK) structure is formed, when the polymer-nanorod interaction (Eb/Ec) is -0.4. For the system with 128 chains, a NHSK structure is formed, when Eb/Ec is -1.0. For the system with 252 chains, NHSK structure cannot be formed. The findings in this work can supply important theoretical reference for the design, preparation, and application of polymer nanocomposites.